Peran Majelis Nyai dalam Pembentukan Disiplin Santri (Studi Kasus di Tarbiyatul Mu’allimien Al-Islamiyah TMI Putri Al-Amien Prenduan) - Ika Mutmainnah; Fayruzah El-Faradis (Jurnal Ilmiah Wahana Pendidikan, 2023)
The nyai assembly is the caretaker of the female Islamic boarding school and nyai has an important role in every activity. The rules that are made must be obeyed and the prohibitions must be obeyed by all students. To comply with all existing regulations, Santri must have an attitude of discipline. The formation of discipline here cannot be separated from the role of Nyai as caregivers in it, so that students can carry out all existing regulations sincerely and consciously. The goal of this study is to describe how the role of nyai in forming the discipline of student and what are the supporting and inhibiting factors for Nyai in forming the discipline of student at Al-Amien Prenduan. The method used is the method of observation, interviews and documentation. The role of the Nyai assembly in Tarbiyatul Mu'allimien Al-Islamiyah (TMi) includes 4 things, namely: As a role model or uswatun hasanah, As a guide, As an advisor, As a controller. According to the researcher's review, there are factors that supporting and inhibiting the role of the Nyai assembly in it. The supporting factors are: the Nyai as example and a role models for Students. Female students is aware of the disciplinary rules and administrators set a good example of the rules that have been set. While the inhibiting factors are: new students who have not been able to adapt to regulations that are different from their home environment, administrators who do not set an example about the disciplinary rules that have been determined and the location of the residence of the Nyai assembly which is outside the hut and the age factor of the Nyai assembly which is no longer young